(3GdTbGFb GdfYeGfjI aj YdeGA GdOhdI GdYKeGfjIs - (3GdJQcj, CHh GdNjQ, WGTcHQj RGOg, YUGe GdOjf, CMeO Hf eUWai Hf Ndjd, (B968 (3g`s
(3ChdgG (B:s
(3GdMeO ddg GdPj QaY HaVdg WHbGJ GdYdeGA cfJ eTZhaG HJJHY efGbH GdYdeGA hCNHGQge heJgGdcG Ydi MaX eBKQge MJi GLJeY ef Pdc TjA cKjQ aj GdNGWQ GdaGJQ HMjK jeJdF HgG HWhf GdcJH s
(3BNQgG (B:s
(3hefge GdTjN GdUGdM eUdM GdOjf eUWai ef Nda GdSjO CMeO GdHNGQj hcJHJ dcd efgG QSGdI Jfja Ydi KdGKjf EdG Cf UhGQa GdCjGe HJbOjQ Gdedc GdYdGe bO GNJQeJgG Jes
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\257s
(3cTa GdXfhf (B2/1057s
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdJGQjNs